Utility function for monetary gains (and losses) satisfying Friedman-Savage hypothesis - Lahiri, Somdeb (Journal of Mathematical Economics and Finance; Vol 8 No 1 (2022): JMEF, Volume VIII, issue 1(14), Summer 2022DO - 10.14505/jmef.v8.1(14).02, 2022)
In this note we provide a closed form utility function for gains that is S-shaped around the origin and satisfies the Friedman-Savage hypothesis. We obtain the corresponding Arrow–Pratt measure of absolute risk aversion (ARA) as well as Arrow–Pratt measure of relative risk aversion (RRA) for it.